Definition of Urban, Highway and Combined Driving Cycles for the city of Quito - Ecuador - Llanes-Cedeño, Edilberto Antonio; Rodriguez-Munive, Mateo Esteban; López-Villada, Jesús; Bustamante-Villagómez, Diego Fernando; Pino-Tarragó, Julio César (International Journal of Membrane Science and Technology, 2023)
The use of driving cycles is a widely accepted method for evaluating fuel consumption and vehicle emissions under specific local conditions. The primary objective of this study was to obtain updated driving cycles that reflect the characteristics of the city of Quito, Ecuador, during peak hours using electronic means to gather driving parameters. To achieve this, the OBD2 ELM327 module and its corresponding mobile application, Car Scanner ELM OBD2, were utilized to record, store, and export real-time data for variables such as vehicle speed, fuel consumption, distance traveled, and travel time, among others, in three zones: urban, highway, and combined. This information enables a comprehensive understanding of the level of vehicle mobility and fuel consumption during peak hours in each zone. The resulting speed vs. time graphs for the selected routes demonstrate the lowest mobility and highest consumption in the urban zone in comparison to the highway and combined zones in terms of kilometers traveled.